Marketing – Temeljni koncepti in njihova uporaba v digitalnem okolju: Praktikum - Iršič, Matjaž; Malc, Domen; Milfelner, Borut; Selinšek, Aleksandra (University of Maribor Press, 2021)
Marketing - Fundamental Concepts and their Use in Digital Environment: Practicum. The handbook is intended for first year undergraduate students at Faculty of Economics and Business for work in the course Fundamentals of marketing and it is used as a supplement to second edition of the monograph Marketing – Fundamental concepts and their use in digital environment. In a total of 10 chapters, this handbook covers basic areas of marketing science: definition of marketing, marketing environment, fundamental marketing concepts, consumer studies, marketing research, marketing strategy planning, product, price, marketing channels and marketing communication. Each chapter follows the same structure: case study, case questions, questions for repetition, exercises for repetition, which allow for deep reflection on the topic.